An update on national recommendations for the use of the adjuvanted recombinant zoster vaccine: Romy Weller. (25th October 2022) - Parikh, R; Widenmaier, R; Weller, R; Lecrenier, N
Abstract: Background: The adjuvanted recombinant zoster vaccine (RZV), first approved in 2017, has high, long-lasting efficacy against herpes zoster (HZ) and a clinically acceptable safety profile. In addition to the prevention of HZ in adults aged ≥50 years, the non-live RZV can be used from age 18 years in individuals with immunocompromised (IC) conditions. We reviewed the evolving landscape of national recommendations for RZV use. Methods: National health authority and vaccination committee websites of countries where RZV is approved were searched in March 2022. Results: Of 41 countries where RZV is licensed, 14 (Australia, Austria, Canada, Czech Republic, Germany, Ireland, Italy, Netherlands, New Zealand, Saudi Arabia, Spain, Switzerland, UK, US) provide national recommendations related to RZV; the majority are preferential to RZV or only recommend RZV. Overall, seven and seven countries recommend immunisation from age 50 years or 60/65 years, respectively. Of the seven countries that recommend immunisation from age 60/65 years, five recommend immunisation in individuals from age 50 years with comorbidities/IC conditions. Five countries recommend immunisation from age 18/19 years in individuals at increased risk of HZ due to immunosuppressive disease/treatment. In addition, six national recommendations refer to RZV safety and nine address prior HZ vaccination and/or infection. All recommendations outlined the RZV administration schedule. Conclusions: Although national recommendations can inform decision making in clinical practice, RZV recommendations are not available in all licensed countries. The recommendations highlight a trend in favour of the use of RZV for the prevention of HZ in older individuals and those with IC conditions. Main messages: An increasing number of countries are providing recommendations for the use of RZV for the prevention of HZ in older individuals and those with IC conditions. Key messages:  An increasing number of countries are providing recommendations for the use of RZV for the prevention of HZ in older individuals.  An increasing number of countries are providing recommendations for the use of RZV for the prevention of HZ in IC conditions.